Peran Orang Tua Terhadap Motivasi Belajar Siswa - Khaerunnisa Yulia Handayani; Mawardi; Sunaryo (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to describe the role of parents in increasing the learning motivation of fifth grade students through a qualitative approach. Through in-depth interviews and participatory observations, this study explores more deeply the various roles of parents, such as role model, motivators, facilitators and evaluators and their influence on students' learning motivation, both intrinsic and extrinsic motivation. The results of the study indicate that the role of parents as motivators is very significant in increasing students' learning motivation. In addition, this study also identified other factors that influence learning at home. The implication of this study is the importance of the role of parents in creating a conducive learning environment and providing sufficient emotional support for students.